The Effectiveness of Giving Crystal Guava Juice (Psidium guajava L. “Crystal”) on Haemoglobin Levels in Female Adolescents with Anaemia - Mayasari, Devi Ratna; Sari, Yulia; Febrinasari, Ratih Puspita (International Journal of Human and Health Sciences (IJHHS), 2023)
Anaemia is one of the health problems in female adolescents with haemoglobin levels in the blood circulation is below normal, which is <12 g/dl at the adolescent threshold. Crystal guava is a fruit that is rich in iron and vitamin C, which helps increase haemoglobin levels in the blood. This study aims to analyse the effectiveness of giving crystal guava juice (Psidium guajava L.“Crystal”) on haemoglobin levels in female adolescents with anaemia. The design of this study was a quasi-experiment with pre and post-test control group design with 36 subjects divided into 3 group. This study was tested using SPSS version 25 with a significant level of 0.05. The result showed that there was an effect of giving crystal guava juice on haemoglobin levels in female adolescents with anaemia by p=0.018 (p<0.05). Giving crystal guava juice with iron tablets is effective to increase haemoglobin levels in female adolescents with anaemia. International Journal of Human and Health Sciences Vol. 07 No. 02 Apr’23 Page: 176-182